Heterogeneous stress field in the source area of the 2003 M6.4 Northern Miyagi Prefecture, NE Japan, earthquake. Issue 1 (21st April 2016) - Yoshida, Keisuke; Hasegawa, Akira; Okada, Tomomi
Abstract: We investigated a detailed spatial distribution of principal stress axis orientations in the source area of the 2003 M6.4 Northern Miyagi Prefecture earthquake that occurred in the forearc of northeastern Japan. Aftershock hypocentres were precisely relocated by applying the double difference method to arrival time data obtained at temporary stations as well as at surrounding routine stations. We picked many P -wave polarity data from seismograms at these stations, which enabled us to obtain 312 well-determined focal mechanism solutions. Stress tensor inversions were performed by using these focal mechanism data. The results show that quite a lot of focal mechanisms are difficult to explain by the uniform stress field, especially near the large slip area of the main-shock rupture. Stress tensor inversions at the location of individual earthquakes show that σ1  axes are orientated mainly to WSW–ENE in the northern part of the source area, while they are oriented to NW–SE in the southern part. This spatial pattern is roughly similar to those of the static stress change by the main shock, which suggests that the observed spatially heterogeneous stress field was formed by the static stress change. If this is the case, the deviatoric stress magnitude before the main shock was very small. Another possibility is the heterogeneous stress field observed after the main shock had existed even before the main shock, although we do not know why it was formed. Unfavourable orientation of the main shock fault with respect to this stress field suggests that the fault is not strong in this case too.